Gabungan Model-Model Pembelajaran Kooperatif Berpotensi Memberdayakan Hasil Belajar Bakteriologi Mahasiswa - Didimus Tanah Boleng (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
A quasi-experimental research has been done in the city of Samarinda. The study applied combined  of Cooperative Script (CS) and Think-Pair-Share (TPS)  learning models on students who took a course Bacteriology. Two classes are used, one class for applied the combined CS- TPS learning model, in another class for applied to conventional learning, during the even semester of the 2015/2016 academic year. Research focuses on knowing the effect of the combined application of CPS-TPS learning model in empowering the cognitive learning and critical thinking skills. Sample was taken by purposive sampling based on the value of protists student, and obtained a total of 32 pairs of students. Retrieving data using assay, conducted on pre-test and post-test. Analysis of the data using the t test for paired samples with significance level of 5% (p˂0,05). The results of data analysis showed that the t value for the cognitive  learning is 2.21; and critical thinking skills is 2.10. T table (df = 32 + 32-2, α = 0.05) is 2.00. The application of combined of CPS-TPS learning model empowering influential in   bacteriological student learning outcomes. Keep in similar studies in the future to obtain more information.Key Word         : Cooperative Script, Think-Pair-Share, Cognitive Learning Outcomes, Critical Thinking Skills, Bacteriology